2018
DOI: 10.1097/j.pain.0000000000001419
|View full text |Cite
|
Sign up to set email alerts
|

Dual enkephalinase inhibitor PL265: a novel topical treatment to alleviate corneal pain and inflammation

Abstract: Ocular pain is a core symptom of inflammatory or traumatic disorders affecting the anterior segment. To date, the management of chronic ocular pain remains a therapeutic challenge in ophthalmology. The main endogenous opioids (enkephalins) play a key role in pain control but exhibit only transient analgesic effects due to their rapid degradation. The aim of this study was to explore the antinociceptive and anti-inflammatory effects of topical administration of PL265 (a dual enkephalinase inhibitor) on murine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…Monitoring c-Fos, ATF3, and c Jun immunopositive cells is a commonly used approach to studying the activation and damage of primary sensory neurons from dorsal root and trigeminal ganglia. cFos, c-Jun, and ATF3 protein expressions were shown to be increased in the ipsilateral TG from animals with corneal damage (De Felipe and Belmonte, 1999;Launay et al, 2016;Fakih et al, 2019;Reaux-Le Goazigo et al, 2019). Both CGRP and ATF3 protein expressions in TG cell bodies increased after injury and returned to a normal level by 1 week, paralleling the time course of changes in nociceptive responses (Hegarty et al, 2018).…”
Section: Molecular and Functional Changes In Trigeminal Corneal Neuromentioning
confidence: 87%
See 2 more Smart Citations
“…Monitoring c-Fos, ATF3, and c Jun immunopositive cells is a commonly used approach to studying the activation and damage of primary sensory neurons from dorsal root and trigeminal ganglia. cFos, c-Jun, and ATF3 protein expressions were shown to be increased in the ipsilateral TG from animals with corneal damage (De Felipe and Belmonte, 1999;Launay et al, 2016;Fakih et al, 2019;Reaux-Le Goazigo et al, 2019). Both CGRP and ATF3 protein expressions in TG cell bodies increased after injury and returned to a normal level by 1 week, paralleling the time course of changes in nociceptive responses (Hegarty et al, 2018).…”
Section: Molecular and Functional Changes In Trigeminal Corneal Neuromentioning
confidence: 87%
“…Activation of SGCs is characterized by GFAP upregulation in the injured trigeminal nerve branch associated with the development of hyperalgesia (Vit et al, 2006;Katagiri et al, 2012), but this has not been observed under non-pathological conditions (Shinoda et al, 2019). Interestingly, increased spontaneous pain behavior and corneal allodynia have been associated with morphological changes (hypertrophy) and upregulation of GFAP protein expression in the SGCs at the level of the ipsilateral trigeminal nerve V1 branch in preclinical models of corneal injury (Launay et al, 2016;Fakih et al, 2019;Reaux-Le Goazigo et al, 2019).…”
Section: Molecular and Functional Changes In Trigeminal Corneal Neuromentioning
confidence: 99%
See 1 more Smart Citation
“…The microscope was calibrated with samples from the sham mice before acquisitions of those from the DED mice. For the quantitative analysis of GFAP, Iba1, and Piccolo immunoreactivity, TG and TBSC sections were analyzed under epifluorescence microscope using a × 20 objective and the same camera parameters (Axio Vision ImagerM1; Carl Zeiss) as previously described [35]. Five ipsilateral TBSC and TG sections per animal were used for the DED and sham animals.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, inhibition of both enzymes has been successfully tested in animals [22], but only with intrathecal application in humans [23]. Progression of enkephalin inhibitors has been discussed [24], and there is sparse but ongoing development for analgesia [25]. Pharmacological intervention with opioids leads to analgesia via a reduction in neuronal excitability [26].…”
Section: Opioid Receptorsmentioning
confidence: 99%